The Functional Role of Calcineurin in Hypertrophy, Regeneration, and Disorders of Skeletal Muscle - Sakuma, Kunihiro (Hindawi Publishing Corporation, 2010)
Skeletal muscle uses calcium as a second messenger to respond and adapt to environmental stimuli. Elevations in intracellular calcium levels activate calcineurin, a serine/threonine phosphatase, resulting in the expression of a set of genes involved in the maintenance, growth, and remodeling of skeletal muscle. In this review, we discuss the effects of calcineurin activity on hypertrophy, regeneration, and disorders of skeletal muscle. Calcineurin is a potent regulator of muscle remodeling, enhancing the differentiation through upregulation of myogenin or MEF2A and downregulation of the Id1 family and myostatin. Foxo may also be a downstream candidate for a calcineurin signaling molecule during muscle regeneration. The strategy of controlling the amount of calcineurin may be effective for the treatment of muscular disorders such as DMD, UCMD, and LGMD. Activation of calcineurin produces muscular hypertrophy of the slow-twitch soleus muscle but not fast-twitch muscles.